Development of critical thinking variable instruments in student worksheet media - Radeswandri Radeswandri; Dindawini Salsabilla; Rian Vebrianto; Mery Berlian; Susilawati Susilawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
In the 21st Century, students' critical thinking abilities are needed to utilize their knowledge in problem-solving. Also, these skills are very important for students in making decisions when faced with various choices. This study aimed to see the effectiveness of students' critical thinking variables in the learning process. This study used a Research and Development (RND) method with an instrument in the form of a questionnaire consisting of 2 constructs. This study was carried out by involving seven teachers from several schools. Data collection was carried out by filling out an online questionnaire. Data were then analyzed with the help of the SPSS program. The results of this study prove that the preparation and development of the evaluation instrument of critical thinking variables in student worksheet media for students in this study were carried out by testing two research constructs, namely accuracy and effectiveness variables. Furthermore, the results of testing the validity and reliability indicate that the data validity of the evaluation instrument meets the valid criteria. Also, the results of this study indicate that the instrument developed meets the requirements for use in the development of student worksheet media.